Assessment of climate change impacts and land cover dynamics in the Upper Sakarya Basin, Türkiye using the Collect Earth approach - Ateşoğlu, Ayhan; Bulut, Fidan Sevval; Özel, Halil Barış; Cetin, Ilknur Zeren; Varol, Tuğrul; Varol, Tuğrul; Özel, Halil Barış; Bulut, Fidan Şevval (Springer Int Publ Ag, 2025)
Long-term monitoring and evaluation of climate change effects in a basin help identify trends, assess ecosystem resilience, and guide adaptive management for sustainable resource use and conservation. The Upper Sakarya Basin (USB), which has the ability to represent semiarid areas of Turkey due to its climate and environmental conditions and land use integrity, was selected as the study area. The study focused on Land Cover and Land Use Transformations, soil moisture, evapotranspiration, Normalized Difference Vegetation Cover (NDVI), Net Primary Production (NPP), water deficit criteria in the basin for a 20-year period (2000-2020) in order to support adaptive management and conservation strategies and to evaluate the effects of climate change on ecosystem dynamics, water balance and vegetation health. As a field monitoring and evaluation method, Collect Earth (CE), which is a sample-based visual interpretation method, was selected because it can better explain the complex structure of land cover types and provides the opportunity to easily access and interpret many graphical data through the GEE code editor. In the context of Land Use, Land-use Change and Forestry (LULUCF), it was observed that the increase in Forestland was due to afforestation activities in Grassland. Although this situation was observed in NDVI observations, it was not evaluated as a net gain area compared to the past situation of Forestland in terms of the ecosystem and the services they provide. It was determined that the conversion to Settlement in the basin was rapid and large in area. As an indicator of vegetation productivity, it was determined that the areas with decreasing trend in NPP were Forestland and Settlement. According to water deficit data, it was determined that water deficit was high in regions where intensive agriculture was carried out in the basin. Evapotranspiration value was continuously increasing for the basin in general, while soil moisture was on a decreasing trend. These findings emphasize the vulnerability of the basin to climate change and emphasize the need for sustainable land and water management strategies. It is recommended that decision makers at the basin scale develop policies based on these findings and evaluate interventions within the framework of a balancing approach against land degradation.
Keywords: Collect Earth; Climate Change; Ecosystem Vulnerability; Semi-Arid Areas; Residential Areas Transition; Balancing Approach